Variable sensitivity of a feline embryo cell line and of three kitten kidney cell cultures to feline herpes- and caliciviruses - Tham, Kok Mun; Studdert, Michael J. (Elsevier, 1986)
The number of plaques produced in a feline embryo (FEmb) cell line and in three independently derived kitten kidney (KK) cell cultures varied in a consistent and reproducible manner when each was inoculated with the same number of feline herpesvirus 1 (FHV1) plaque forming units (PFU); the three KK cells produced 2-9 times more plaques than FEmb cells. One of the three KK cells produced FHV1 plaques that were smaller in diameter than those FEmb cells. Each of the three KK cell cultures inoculated with the same number of FEmb cell PFU of a strain of feline calicivirus (FCV) produced different numbers of plaques; two of the three KK cell cultures produced 2-3 times more plaques than FEmb cells. The plaque diameter of FCV in the three KK cells was 30-50% smaller than the plaque diameter in FEmb cells.